Implikasi Tradisi Mabbaca Unti dalam Mendukung Pendidikan Karakter di SMA Negeri 9 Marusu - Sakmawati Sakmawati; Salwia Salwia (Universitas Methodist Indonesia, 2026)
This study aims to analyze the implications of the Mabbaca Unti tradition in supporting character formation and strengthening students' cultural identity at SMA Negeri 9 Marusu, Maros Regency. Using a qualitative approach with a case study type, data were obtained through observation, in-depth interviews, and documentation involving the principal, teachers, students, and traditional leaders. The results of the study show that Mabbaca Unti not only functions as a ceremonial ritual but has also been integrated as a school culture that contains religious values, social solidarity, responsibility, and discipline. Theoretically, this tradition can be understood as a rite of passage that strengthens students' mental readiness as well as a mechanism for forming collective solidarity between the school, family, and community. The cultural values contained within it transform into psychological and social capital that supports students' motivation and academic resilience. The integration of local wisdom in formal education shows that tradition and modernity can go hand in hand in shaping a generation that has character and is rooted in local cultural values.